Legal Regulation of Technical Expertise Procedures in proving written Forgery in Palestinian Legislation - Saleh Samih Al Samna; Abdul Fattah bin Wan Ismail (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
Technical expertise is considered one of the important issues that should be highlighted due to its importance in criminal matters in general, and cases of proving forgery in particular. This study aims primarily to shed light on the extent to which the Palestinian legislator organizes the procedures of technical expertise in proving forgery. Linear, as the importance of the study highlights the analysis of the Palestinian legislative reality in how to combat the crime of forgery of official documents and ways to confront it by stating the procedures of the technical expert to reveal the areas of forgery in written documents. This study discusses the main problem represented in the extent to which the texts of Palestinian legislation organize the rules governing technical expertise and its procedures in proving a forgery claim. To achieve the purpose of the study, the researchers followed the analytical approach, where they analyzed the legal texts regulating the provisions of technical expertise and its procedures in proving a written forgery claim, by examining the law Evidence and the Criminal Procedures Law, and analyzing the content and substance of those legal texts that directly or indirectly addressed provisions and issues related to written expertise, sorting them out and discussing them scientifically, in addition to analyzing the statements and opinions presented by scholars and researchers specializing in their study of aspects of this topic.